Enhancing Textile Cotton Yarn Sizing: Investigating Factors Impacting Breaking Strength, Pick-Up Percentage, and Elongation Loss - Derseh Yilie Limeneh; Million Ayele; Mesfin Shiferaw Wubie; Addisu Ferede Tessema; Noureddine Abidi; Zelalem Adane Alemar (Journal of Natural Fibers)
The paper investigates the effect of machine setting on breaking strength, breaking elongation, and pick-up percentage of sized yarn properties. The factors considered are concentration of size solution, squeezing pressure and counts of yarn, the aim to develop a regression model that shows the effect of factors on size pick-up percentage, breaking strength regain, and loss in breaking elongation. The experiment is conducted by using 16 Ne and 21 Ne of cotton yarn, 3 Bar and 5 Bar of squeezing pressure, and 1.9% and 6% of size concentration with maize starch as sizing agent. A factorial design with two factors and 5 replicants has been used to design the experiment and analyze the results. The result showed that a slight change in squeezing pressure and concentration significantly affects the pick-up percentage, breaking strength regain and breaking elongation loss while a change of yarn count would not have a significant effect on the pick-up percentage of sized yarn. Furthermore, for achieving optimum properties of the sized yarn the pressure of squeezing, the count of the yarn and the concentration of the solution should be adjusted, and a regression model is developed to investigate the properties of the sized yarn by considering considered factors.